The role of sunscreen in melasma and postinflammatory hyperpigmentation - Fatima, Sakeena; Braunberger, Taylor; Mohammad, Tasneem; Kohli, Indermeet; Hamzavi, Iltefat (Indian journal of dermatology, 2020)
Photosensitive conditions such as melasma and postinflammatory hyperpigmentation (PIH) are exacerbated by exposure to ultraviolet (UV) rays and visible light making sunscreen use an essential component of treatment. This is especially true in skin of color patients who are less likely to use photoprotection, even if diagnosed with these photoexacerbated conditions. We aimed to evaluate the body of literature to provide evidence for the use of sunscreen in the treatment of melasma and PIH. We reviewed English articles from PubMed, Journals@Ovid Full Text, and Embase using the search terms "sunscreen" and either "melasma" "PIH," or "post-inflammatory hyperpigmentation." Nine relevant publications provide evidence that a broad spectrum of protection, including UVA, UVB, and visible light within sunscreens can play an adjuvant role in therapy for melasma and PIH by stabilizing and improving these pigmentary disorders in skin of color patients. This review illustrates the advantages and limitations of sunscreen use, as well as practice gaps in photoprotection in the skin of color patients with melasma and PIH.